2011
DOI: 10.1111/j.1745-3933.2011.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the polarization of anomalous microwave emission in nearby molecular clouds

Abstract: Anomalous microwave emission (AME) has been previously studied in two well-known molecular clouds and is thought to be due to electric dipole radiation from small spinning dust grains. It is important to measure the polarization properties of this radiation both for component separation in future cosmic microwave background (CMB) experiments and also to constrain dust models. We have searched for linearly polarized radio emission associated with the ρ Ophiuchi and Perseus molecular clouds using WMAP 7-year dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…The best constraint comes from the Perseus region, which has significant AME emission and relatively little contaminating synchrotron emission. Battistelli et al (2006) reported a weak detection in Perseus at 3.4 +1.5 −1.9 % at 11 GHz, while later measurements obtained by López-Caraballo et al (2011) using WMAP data found a 2σ limit of <1%; Dickinson et al (2011) have also measured a 2σ limit of <1.4% for Perseus (as well as an upper limit of <1.7% in ρ Ophiuchus), and Génova- Santos et al (2015) found a 2σ limit of <2.8% in Perseus at 19 GHz. Recently, Battistelli et al (2015) have claimed to detect polarized AME emission at 21.5 GHz from RCW 175, an H ii region, where they measured a polarization percentage of (2.2 ± 0.2 (random) ± 0.3 (systematic))% at 21.5 GHz.…”
Section: Limits On Ame Polarizationmentioning
confidence: 98%
“…The best constraint comes from the Perseus region, which has significant AME emission and relatively little contaminating synchrotron emission. Battistelli et al (2006) reported a weak detection in Perseus at 3.4 +1.5 −1.9 % at 11 GHz, while later measurements obtained by López-Caraballo et al (2011) using WMAP data found a 2σ limit of <1%; Dickinson et al (2011) have also measured a 2σ limit of <1.4% for Perseus (as well as an upper limit of <1.7% in ρ Ophiuchus), and Génova- Santos et al (2015) found a 2σ limit of <2.8% in Perseus at 19 GHz. Recently, Battistelli et al (2015) have claimed to detect polarized AME emission at 21.5 GHz from RCW 175, an H ii region, where they measured a polarization percentage of (2.2 ± 0.2 (random) ± 0.3 (systematic))% at 21.5 GHz.…”
Section: Limits On Ame Polarizationmentioning
confidence: 98%
“…Fig. 15.-Measured polarization of AME from the Perseus molecular complex (Battistelli et al 2006;Dickinson et al 2011); the dark clouds Lynds 1622 (Mason et al 2009) and ρ Oph (Dickinson et al 2011); the HII regions G159.6-18.5 (López-Caraballo et al 2011;Génova-Santos et al 2015) and RCW176 (Battistelli et al 2015); and the W43r molecular complex (Génova-Santos et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Anomalous microwave emission (AME), which is observed at WMAP frequencies shows little polarisation. Dickinson, Peel & Vidal (2011) set upper limits of less than 2.6% on the polarisation of two AME regions (see Rubiño-Martín et al (2012) for a recent review of AME polarisation measurements).…”
Section: Polarised Spectral Indicesmentioning
confidence: 99%